(untitled) (Hamburger Journal für Kulturanthropologie (HJK), 2018)
How can artistic creative practice be combined with ethnological cultural analysis? A process based on practices of art probing is proposed and related to discussions about museum imaginaries, digital cultures and sensory aspects of ethnography. The point of departure for the discussion is the audiovisual performance Possible Worlds.